Experimental results of gaslift process - Hai, Duong Ngoc; Thien, Nguyen Duy; Canh, Nguyen Van (Vietnam Journal of Mechanics, 2008)
In the paper, the investigation results of periodical gas-lift flows in vertical pipes using experiment method are presented. The experiment facilities consist of flow measurement equipment, gas and fluid supplier facilities, tubing system. To study the influence of medium physical and dynamical characteristics on the process efficiency, two liquid-gas systems are used, namely, water-air and spindle oil-air. The objects of investigation are to obtain data from tests conducted in some conduits and to analyse the influence of system physical, geometrical and etc. parameters such as: initial liquid height in the conduits, gas injected volume, conduit diameter, conduit configuration and etc. on the considered process